Healthcare scandals in the NHS: crime and punishment. Issue 4 (31st January 2011) - Alghrani, Amel; Brazier, Margaret; Farrell, Anne-Maree; Griffiths, Danielle; Allen, Neil
Abstract : The Francis Report into failures of care at Mid Staffordshire NHS Foundation Trust Hospital documented a series of 'shocking' systematic failings in healthcare that left patients routinely neglected, humiliated and in pain as the Trust focused on cutting costs and hitting government targets. At present, the criminal law in England plays a limited role in calling healthcare professionals to account for failures in care. Normally, only if a gross error leads to death will a doctor or nurse face the prospect of prosecution. Doctors and nurses caring for patients under the Mental Health Act 1983 and the Mental Capacity Act 2005 may however be prosecuted for wilful neglect of a patient. In the light of the Francis Report, this article considers whether the criminal offence of wilful neglect should be extended to a broader healthcare setting and not confined to mental healthcare.